Evaluasi Kinerja Pemeliharaan PLTA dengan Pendekatan Maintenance Scorecard dan Objective Matrix (OMAX) (Studi Kasus Unit Pembangkit Listrik Tenaga Air Maninjau) - Taufik; Afrizal (Jurnal Optimasi Sistem Industri, 2014)
Hydropower is one of the power plants that supplies electrical energy. It has several machines and equipment that have a time limit of use. To anticipate the limitation of the use, maintenance of machinery and equipment are needed in order to return its original state and can perform its function as usual. Therefore some indicators required to determine maintenance work performance level to provide the optimal results. The Traditional measurement methods have some limitations that make it difficult to implement in industrial environments. This requires a performance measurement method that can provide a balanced perspective on the overall system performance. One of them is implementing the Maintenance Scorecard and Objective Matrix (OMAX) method to assess the performance of hydropower maintenance. Objective research in this assessment is to integrate Maintenance Scorecard and Objective Matrix (OMAX) approach in Maninjau Hydropower. Key Performance Indicators (KPI) are defined by 6 perspectives: productivity perspective, cost effectiveness perspective, a safety perspective, an environmental perspective, quality perspective and learning perspective. The priorities are determined by using Analytical Hierarchy Process (AHP). We then measure the performance of maintenance by using Objective Matrix (OMAX) until we get the level of achievement of the performance in the current situation.The results obtained in the process of designing the scorecard maintenance on the Maninjau hydropower that produces overall 20 KPI consists of 9 KPI for productivity perspective, 4 KPI for quality perspective, 2 KPI for safety perspective, 2 KPI for environmental perspective and 3 KPIs for learning perspective. There are 5 KPIs for corporate level, 8 KPIs for strategic level and 7 KPIs functional level. The operation results show the number of KWH that produced, Capacity Factor and Equivalent Outage Force Factor are in the yellow zone. It means the attentions and improvements are needed to improve performance in the next period.